Medical conditions, health status, and health services utilization. - Pope, G C (1988)
Using data from the 1980 National Medical Care Utilization and Expenditure Survey (N = 11,530), four commonly used health status indicators are interpreted in terms of the underlying medical conditions they reflect. It is found that self-rated health status, role limitations, restricted activity days, and functional limitations measure similar conditions. These conditions tend to be chronic and severe; heart and cerebrovascular disease are especially associated with poor health as measured by all of the variables. Disability days is most likely to reflect acute, transitory morbidity. Practical suggestions for the appropriate use of the four variables are made. In addition, the conditions associated with the most ambulatory utilization of health services are identified. Among these conditions, those which are and are not measured adequately by the health status indicators are disclosed. It is concluded that the health status variables, either individually or as a group, do not measure many variations in health that are strongly related to utilization.